Concluding thoughts: new philanthropy, age-old problems (2019)
As Northern philanthropic foundations, particularly those from North America, have extended their reach and activities into the Global South, it is clear that many of the problems that have historically plagued the development sector are now being encountered by the philanthropic sector. The chapters in this volume reveal that philanthropic organisations working in education globally are facing a variety of similar challenges, including a North–South divide, issues related to collaboration, the growing influence of the private sector and a need for greater transparency. In the following sections, I will discuss each of these areas in turn before concluding with some thoughts on where future research on global trends in philanthropy and education might go next.